Quantitative Estimation on Contribution of Climate Changes and Watershed Characteristic Changes to Decreasing Streamflow in a Typical Basin of Yellow River - Lv, Xizhi; Liu, Shanshan; Li, Shaopeng; Ni, Yongxin; Qin, Tianling; Zhang, Qiufen (Frontiers in Earth Science, 2021)
Climate changes and underlying surface of the watershed have affected the evolution of streamflow to a different degree. It is of great significance to quantitatively evaluate main drivers of streamflow change for development, utilization, and planning management of water resources. In this study, the Huangshui River basin, a typical basin of the Qinghai-Tibetan Plateau, China, was chosen as the research area. Huangshui is the largest first-class tributary in the upstream of the Yellow River. Based on the Budyko hypothesis, streamflow and meteorological datasets from 1958 to 2017 were used to quantitatively assess the relative contributions of changes in climate and watershed characteristics to streamflow change in research area. The results show that the streamflow of Huangshui River basin shows an insignificant decreasing trend; the sensitivity coefficients of streamflow to precipitation, potential evapotranspiration, and watershed characteristic parameter are 0.5502, −0.1055, and −183.2007, respectively. That is, 1 unit increase in precipitation would induce an increase of 0.5502 units in streamflow, and 1 unit increase in potential evapotranspiration would induce a decrease of 0.1055 units in streamflow, and an increase of 1 unit in the watershed characteristic coefficient would induce a decrease of 183.2007 units in streamflow. The streamflow decreased by 20.48 mm (13.59%) during the change period (1994–2017) compared with that during the reference period (1958–1993), which can be attributed to watershed characteristic changes (accounting for 73.64%) and climate change (accounting for 24.48%). Watershed characteristic changes exert a dominant influence upon the reduction of streamflow in the Huangshui River basin.